Estudo da viabilidade econômica da implantação de uma indústria de biogás a partir de dejetos suínos em Francisco Beltrão-PR - Rosa, Matheus Lucca Goulart (2022)
In order to generate work that could bring economic returns to the region of Francisco Beltrão-PR, a scenario was determined in which biogas could be an alternative for this. Faced with a considerable amount of swine waste generated in the region, it was possible to understand that the construction of a business based on the production of energy, from gas, could bring considerable financial returns to the municipality. It is a gas basically composed of methane and carbon dioxide that can be easily generated from the anaerobic fermentation of organic waste. From the combustion of this gas, it is possible to generate electricity in a clean and environmentally correct way. Biogas' high employability, low complexity and flexibility have made it a sustainable and profitable way of doing business. In this sense, the objective of the study was to elaborate a PN to determine how viable this type of enterprise is. For this, it was necessary to build a Business Plan aimed at this type of industry, in addition to a technical study on biogas itself. The methodology used was: Initially, carry out a study on biogas, the biogas industry and PN and, subsequently, apply the PN for the creation of an industry in the determined molds. As a result of the work, it can be seen that the implementation of this industry in the built scenario proved to be viable. The economic and financial viability indicators evaluated were: Break-even point, Profitability, Profitability and Return on Investment Term.